Pengaruh Rolling Massage dan Breast Care Saat Hamil Trimester III Terhadap Pengeluaran ASI di Wilayah Kerja Puskesmas Balai Berkuak: The Effect Of Rolling Massage And Breast Care During The Third Trimester Of Pregnancy On Breast Milk Expenditure In The Work Area Of The Balai Berkuak Health Center - Dayen; Yuni Kusmiyati; Juda Julia Kristiarini (LPPM STIKES Guna Bangsa, 2023)
The nutritional status of children is still low due to a lack of exclusive breastfeeding during infancy. Insufficient breast milk causes mothers to give complementary foods after giving birth. The research objective was to determine the effect of rolling massage and breast care during the third trimester of pregnancy on milk production. The research method used a quasy experiment with a post test only design with control group approach carried out in the working area of ​​the Balai Berkuak Health Center. The sampling method used is random sampling. Samples that met the inclusion criteria were 30 mothers. The sample was divided into 15 respondents in the intervention group and 15 respondents in the control group. Data analysis used univariate, bivariate and multivariate logistic regression. The results of the analysis of the smooth expulsion of breast milk by rolling massage and breast care during the third trimester of pregnancy showed that there was a significant relationship p = 0.003 (p <0.05). Nutrition has a partial effect on breastfeeding expenditure p=0.008 (p<0.05). Rolling massage and breast care during the third trimester of pregnancy on breastfeeding with mothers who were not intervened. The study showed that external psychological factors had a partial effect on breastfeeding, p = 0.025 (p <0.05). Rolling massage and breast care had a significant effect on p=0.002 (p<0.05), the most dominant had a 52 times chance of influencing milk production.